2022
DOI: 10.1002/ejoc.202101171
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Povarov Reactions: An Update of a Powerful Catalytic Synthetic Methodology

Abstract: The enantioselective Povarov reaction is one of the most powerful synthetic strategy to synthesize chiral, highly functionalized 1,2,3,4-tetrahydroquinolines. The present Minireview aims to collect the most significant successful examples of highly efficient enantioselective catalytic protocols for this reaction, since 2014. A comprehensive discussion of different catalytic strategies employed in recent years to realize the enantioselec-tive Povarov reaction is provided; the use of chiral phosphoric acids, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 103 publications
(197 reference statements)
0
14
0
Order By: Relevance
“…The tautomerization of A could generate intermediate B . Then, a stepwise inverse electron-demanding aza-Diels–Alder reaction 16 between A (diene) and B (dienophile) furnished the skeleton of D via intermediate C . In the process of [4 + 2] cycloaddition, two exo attacks occurred successively due to the hindrance effect of the neighboring cyclic isopropylidene, which resulted in the major product with trans conformations between both C-1/C-2 and C-1′/C-2′, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The tautomerization of A could generate intermediate B . Then, a stepwise inverse electron-demanding aza-Diels–Alder reaction 16 between A (diene) and B (dienophile) furnished the skeleton of D via intermediate C . In the process of [4 + 2] cycloaddition, two exo attacks occurred successively due to the hindrance effect of the neighboring cyclic isopropylidene, which resulted in the major product with trans conformations between both C-1/C-2 and C-1′/C-2′, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Examples include the natural There are many synthetic routes to access chiral THQ, 5 but the simplest and most versatile to implement with a multicomponent approach remains the asymmetric Povarov reaction. 10,11 Synthesis of highly optically pure THQs can be achieved by enantioselective Povarov reactions based on a [4+2] cycloaddition or a Mannich/Friedel-Craft sequence mechanism. 4 The seminal work by Kobayashi and co-workers showed that trisubstituted THQ can be obtained in good enantioselectivity with a cis-2,3 and cis-3,4 configuration (Scheme 1, Eq.1).…”
Section: Introductionmentioning
confidence: 99%
“…There are many synthetic routes to access chiral THQ, [5] but the simplest and most versatile to implement with a multicomponent approach remains the asymmetric Povarov reaction [10,11] . Synthesis of highly optically pure THQs can be achieved by enantioselective Povarov reactions based on a [4+2] cycloaddition or a Mannich/Friedel‐Craft sequence mechanism [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The Povarov reaction, which is a commendable means to build ring system from simple and readily available substrates, has been demonstrated to be one of the most attractive approaches in the construction of chiral molecules containing quinoline units. [54][55][56][57][58][59][60][61][62] We speculated that chiral Bronsted acid catalyzed Povarov reaction followed with the subsequent oxidative aromatization process can synthesize chiral quinohelicenes (Fig. 1D).…”
mentioning
confidence: 99%